S’adapter à la dégradation de l’environnement dans le Delta du Saloum : Variabilité des stratégies chez les femmes socés et niominkas du Sénégal - Marie Fall (VertigO)
The population of Saloum Delta belongs to the Soce’s and Niominka’s ethnic groups. Installed in Betenti and Niombato islands, Soce’s main activities are agriculture, fisheries and trade. In Saloum islands, the Niominkas practice the same activities. Depending on natural resources, niominka’s and soce’s women have seen their activities disrupted by the degradation of ecosystems. The collecting of seafood is suffering from the scarcity of the resource. The processing of fish products is adversely affected by the drastic reduction in catches. The decline in rainfall, reduction of water and soil depletion are serious constraints to agricultural activities secondaries but necessary for the survival of the families. Faced with such phenomena on which women have no control, the key word remains for them "cope". We will show in a comparative approach how practices coping with these challenges arise between two groups of women and part of culture in the variability of women's strategies.